RING BERSIH KANAN DAN MODUL BERSIH KANAN - , Cyrenia Novella Krisnamurti; , Dr. Indah Emilia Wijayanti, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This thesis discusses the ring clean, clean module and ring exchange. After that it was shown right clean rings are extension of clean rings and right clean module are extension clean module . Based on the properties of the right clean rings and the properties of the weakly exchange rings obtained every weakly right exchange rings are right clean rings. Keywords : right clean rings, right clean modules, weakly right exchange rings.